Novel Therapeutics in Radioactive Iodine-Resistant Thyroid Cancer - Fullmer, Tanner; Cabanillas, Maria E.; Zafereo, Mark (Frontiers in Endocrinology, 2021)
Iodine-resistant cancers account for the vast majority of thyroid related mortality and, until recently, there were limited therapeutic options. However, over the last decade our understanding of the molecular foundation of thyroid function and carcinogenesis has driven the development of many novel therapeutics. These include FDA approved tyrosine kinase inhibitors and small molecular inhibitors of VEGFR, BRAF, MEK, NTRK and RET, which collectively have significantly changed the prognostic outlook for this patient population. Some therapeutics can re-sensitize de-differentiated cancers to iodine, allowing for radioactive iodine treatment and improved disease control. Remarkably, there is now an FDA approved treatment for BRAF-mutated patients with anaplastic thyroid cancer, previously considered invariably and rapidly fatal. The treatment landscape for iodine-resistant thyroid cancer is changing rapidly with many new targets, therapeutics, clinical trials, and approved treatments. We provide an up-to-date review of novel therapeutic options in the treatment of iodine-resistant thyroid cancer.